Characteristics of Clostridioides difficile colonization in Ilamian children - Sayyadi, M.; Kouhsari, E.; Kalvandi, G.; Kazemian, H.; Ghafouri, Z.; Sadeghifard, N. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The increasing colonization with Clostridioides difficile in paediatric hospitalized population is a well known event; however, its prevalence in Iranian children has not effectively been identified yet. Objective. The objective of this study was to determine the intestinal-carriage rates of C. difficile and molecular characterization of C. difficile in the Ilamian pediatric population from May 22, 2018, until September 22, 2018. Materials and Methods. Eighty samples were obtained from 40 children aged